A Chiral Ligand Assembly That Confers One‐Electron O2 Reduction Activity for a Cu2+‐Selective Metallohydrogel. Issue 13 (23rd February 2018) - Wang, Xiaojuan; Wei, Chuanwan; Su, Ji‐Hu; He, Bo; Wen, Ge‐Bo; Lin, Ying‐Wu; Zhang, Yi
Abstract: The design of functional metallohydrogels is attractive but challenging. A rational approach is introduced for designing functional metallohydrogels using chiral ligands, a phenylalanine derivative with a pyridyl group (l /d ‐PF). Intriguingly, the as‐prepared metallohydrogel exhibits excellent O2 binding and activating properties. Insights into the O2 binding pathway reveals the presence of a novel [(l +d )‐PF‐Cu 3+ ‐O2 − ] species, which can efficiently reduce ferric cytochrome  c with the reactive O2 − by receiving an electron from reductant ascorbic acid. This study provides helpful instructions for developing new artificial systems with specific functions through the effective combination of chiral ligands with metal ions. Abstract : Using both hands : The combination of chiral ligands, a phenylalanine derivative with a pyridyl group (l /d ‐PF), forms a Cu 2+ ‐selective metallohydrogel and exhibits one‐electron O2 reduction activity.